2023
DOI: 10.1002/pmrj.12988
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation service impact on physical function and adherence compared to face‐to‐face rehabilitation in patients with stroke: A systematic review and meta‐analysis

Abstract: PurposeThe purposes of this systematic review and meta‐analysis were to: 1) appraise the available evidence of telerehabilitation program effects on functional outcomes, adherence and patient satisfaction compared to face‐to‐face programs after stroke, and 2) provide direction for future outcome measure selection and development for clinical research purposes.MethodsMEDLINE, CINAHL, Embase, Scopus, Proquest Theses and Dissertations, PEDro, and Clinical Trials.gov were searched for studies published in English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…A Cochrane Review involving studies up to June 2019 indicated no difference between telerehabilitation and in-person rehabilitation regarding activities of daily living based on low certainty evidence. 44 Several SRs pointed to the comparable outcomes of telerehabilitation when compared to in-person traditional rehabilitation on upper extremity function and balance 45 , 46 with strong evidence for balance 47 as well as equivalency in some other outcomes such as Barthel Index 48 and ADL. 49 Guidelines 50 can be consulted for details of providing rehabilitation to individuals with stroke using telecommunication technologies.…”
Section: Resultsmentioning
confidence: 99%
“…A Cochrane Review involving studies up to June 2019 indicated no difference between telerehabilitation and in-person rehabilitation regarding activities of daily living based on low certainty evidence. 44 Several SRs pointed to the comparable outcomes of telerehabilitation when compared to in-person traditional rehabilitation on upper extremity function and balance 45 , 46 with strong evidence for balance 47 as well as equivalency in some other outcomes such as Barthel Index 48 and ADL. 49 Guidelines 50 can be consulted for details of providing rehabilitation to individuals with stroke using telecommunication technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Various VR systems can be used for TR application, which appears to be comparable to conventional in-person rehabilitation in improving motor function [21], especially for upper-extremity and balance recovery among stroke survivors in the chronic stage [18]. This occurs in various functional domains [22,23], also resulting in improvements in cognitive deficits [23], especially for executive function impairments [24], and in patients with post-stroke aphasia [25,26]. In this study, a model for integrated TR was devised with the aim of offering a holistic and patient-centered approach to stroke rehabilitation.…”
Section: Rationale For the Studymentioning
confidence: 99%
“… 10 Telerehabilitation solutions promote therapy adherence after neurological injury and demonstrate equivalent or better outcomes when compared to conventional face-to-face therapy. 11 Additionally, telerehabilitation increases engagement and permits longer courses of rehabilitation, which has been shown to produce additional recovery. 12 , 13 Take-home systems, such as RePlay, have been developed to support high-repetition motor rehabilitation and could be readily combined with strategies to improve VNS stimulation timing.…”
Section: Introductionmentioning
confidence: 99%